Exploring the Concept of Children as a Fitnah in Islamic Family Law: A Deeper Understanding - Luthfi, Moh.; Musdatulia, Musarika; Fauzan, Ahmad; Baihaqi, Yusuf (IJLHE: International Journal of Language, Humanities, and Education, 2024)
In marriage, the presence of a child is one of the greatest blessings granted by Allah SWT to a husband and wife. The arrival of a child can be a source of joy and comfort for the parents, and the child can also be a adornment for both parents. However, it is important to recognize that a child can also become a fitnah for the parents, as mentioned in Q.S. at-Tagābun verse 15. When examining the verses concerning fitnah in the Qur'an, we find that there are many different meanings of fitnah, which may vary significantly when compared to its definition in the Indonesian Dictionary. This study aims to explore the understanding of the concept of "Children as Fitnah" from the perspective of Islamic Family Law. This research is based on the analysis of relevant Qur'anic verses and hadiths, as well as their application in Islamic family law. Furthermore, this article also examines the views of several Tafsir lecturers at UIN Raden Intan Lampung, who refer to various Tafsir interpretations. This study is qualitative in nature, utilizing a descriptive writing technique. The data sources include primary data from the thoughts of Tafsir lecturers referring to various Tafsir interpretations, and secondary data from journals and books related to this concept and its impact on parenting patterns and parental responsibilities in a modern context. The research findings highlight the importance of understanding the rights and responsibilities of each family member and instilling key values in the family, particularly to children from an early age. These include teaching faith and belief, encouraging kindness and affection, promoting regular worship, setting a good example, and providing halal and ṭoyyib sustenance to the family.